PERAN GURU DALAM MENGEMBANGKAN KEMANDIRIAN SISWA MELALUI LAYANAN BIMBINGAN DAN KONSELING DI SEKOLAH DASAR - Sumiyati, Yohana; Pamungkas, Rachmi Wiharyati (TRIHAYU: Jurnal Pendidikan Ke-SD-an, 2020)
This research aims to describe the teachers’ role in developing student's independence through counseling (BK) services at the Suryodiningratan 1 Public Elementary School Yogyakarta in the 2018/2019 school year. This study included qualitative descriptive research. The subjects of this study were the principal, the 1st grade till 6th-grade teachers, 4th grade to 6th-grade students, and their parents. Data collection techniques used observation, interviews, and documentation. The data analysis technique in this study used some steps namely data collection, data reduction, data display, and conclusion drawing. Based on the teachers’ role in developing students’ independence through counseling services at the Suryodiningratan 1 Public Elementary School Yogyakarta in 2018/2019 school year, the results were described in the form of descriptions and tables.